The mediating role of sexual satisfaction in the relationship between personality traits and emotional divorce in men - Mosadegh, Hanieh; Darbani, Seyed Ali; Parsakia, Kamdin (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this study was to investigate the mediating role of sexual satisfaction in the relationship between personality traits and emotional divorce in men. Method: The current research was correlational and descriptive. The statistical population of this research was the men of Tehran in 2022-23. In this study, 263 married men of Tehran were selected as the statistical sample of the research. The measurement tools include Larson's Sexual Satisfaction Questionnaire (1998), Gottman's Emotional Divorce Questionnaire (1998) and the short form of the NEO Questionnaire. Finally, the data collected through the questionnaire was analyzed using the structural equation model and SPSS and AMOS software. Results: The research findings showed that the research model had a good fit and all paths in the research model had significant coefficients. The results of the statistical analysis of the data collected through the questionnaire showed that the mediating role of the marital satisfaction variable in the relationship between personality traits and emotional divorce is significant at the 0.01 level (P < 0.01). Conclusion: In general, based on the findings in the field of emotional divorce, personality characteristics and sexual satisfaction of couples, it can be said that these three variables are related to each other. Examining the relationship between these three in the form of a structural equation model showed that personality traits can help predict emotional divorce and better examine the state of the marital relationship. Therefore, by considering marital satisfaction as a mediating variable, since according to the results obtained in this research, it can strengthen the existing relationship between personality traits and emotional divorce, we can predict emotional divorce with more accuracy and confidence. Therefore, the result obtained from this research can be useful in examining couples' relationships.